2002
DOI: 10.1073/pnas.092258699
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal sinus anatomy of Aegyptopithecus : Implications for hominoid origins

Abstract: The East African Early Miocene apes, or proconsulids, have often been considered to be among the earliest members of the Hominoidea, as defined by the divergence of the Cercopithecoidea, but this hypothesis is only weakly supported by available fossil evidence. The ethmofrontal sinus is one of a few morphological features that may link proconsulids with later hominoids. Here we present direct evidence of an ethmofrontal sinus in an early Oligocene stem catarrhine, Aegyptopithecus zeuxis. The presence of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…The homology between platyrrhine Type 2 frontal sinuses and Paulli's (1900a-c) sinus I' documented above, along with the presence of ethmofrontal sinuses in stem catarrhines (Rossie et al, 2002), leaves no taxic reason to object to a transformational homology between strepsirhine and platyrrhine frontal sinuses and catarrhine ethmofrontal sinuses.…”
Section: Frontal Sinusesmentioning
confidence: 96%
See 1 more Smart Citation
“…The homology between platyrrhine Type 2 frontal sinuses and Paulli's (1900a-c) sinus I' documented above, along with the presence of ethmofrontal sinuses in stem catarrhines (Rossie et al, 2002), leaves no taxic reason to object to a transformational homology between strepsirhine and platyrrhine frontal sinuses and catarrhine ethmofrontal sinuses.…”
Section: Frontal Sinusesmentioning
confidence: 96%
“…It is generally recognized that such ambiguity can only be resolved by considering the anatomy of stem catarrhines such as Aegyptopithecus and Propliopithecus (e.g., Harrison, 1982;Fleagle and Kay, 1983). Accordingly, an investigation of the paranasal anatomy of Aegyptopithecus zeuxis and the early Miocene East African "hominoids" has been undertaken (Rossie et al, 2002;Rossie, 2003a). Character optimization of these combined datasets forms the subject of a forthcoming article (also see Rossie, 2003b).…”
Section: Anthropoideamentioning
confidence: 97%
“…An ethmofrontal sinus occurs in African apes, Proconsul, Morotopithecus, and Afropithecus, and is absent in Pongo, Hylobates, and cercopithecoids. 9 Over the years, this feature has been considered an African ape and human 97 or great ape 1 synapomorphy, as well as an ancestral hominoid character that has been lost in the extant Asian apes and Sivapithecus. 98,99 Recent CT imaging of Aegyptopithecus by Rossie and colleagues 9 has shown that it possessed the sinus, revealing that its presence in Proconsul is plesiomorphic.…”
Section: What Is An Ape?mentioning
confidence: 99%
“…Instead, Proconsul would represent a taxon that tells us more about the primitive catarrhines that predated the hominoids and cercopithecoids than about the primitive hominoid morphotype. 5,9,121 If hylobatids branched after Morotopithecus, they are again dwarf forms; otherwise, if their life history represents a slowing down from the primitive anthropoid condition, they evolved it independently at a small body size. Attempting to decouple slowed life history and large body size is beyond the scope of this paper, but one might speculate that a stable environment or some survivorship advantages afforded by their locomotion could have been selective agents in the small gibbons.…”
Section: What Is An Ape?mentioning
confidence: 99%
“…1e, f). In contrast to the gibbon and orangutan, however, frontal sinuses and ethmoidal air cells are present only in African apes including humans (Cave and Haines 1940), though a recent study of the fossil catarrhine Aegyptopithecus (Rossie et al 2002) suggests that a small frontal sinus may be the primitive condition for Catarrhini.…”
Section: Discussionmentioning
confidence: 99%